Impact of uric acid on immature platelet fraction in patients undergoing percutaneous coronary intervention. Issue 198 (February 2021) - Nardin, Matteo; Verdoia, Monica; Negro, Federica; Tonon, Francesco; De Luca, Giuseppe
Abstract: Introduction: Reticulated platelets have been involved in the pathophysiology of coronary artery disease (CAD). Immature platelet fraction (IPF) allows their measurement in daily clinical practice, although the factors conditioning their elevation are still largely unexplored. Serum uric acid (SUA) is the end product of purine metabolism, displaying a pro-oxidant and pro-inflammatory action and increasing the cardiovascular risk. The aim of our study was to investigate the impact of SUA on IPF levels in patients undergoing percutaneous coronary intervention (PCI), and their relationship with CAD. Methods: We enrolled a cohort of consecutive patients undergoing coronary angiography in a single center. Hyperuricemia was defined by SUA ≥ 6.5 mg/dl. Significant CAD was defined as at least 1 vessel stenosis >50%, while severe CAD was defined as left main and/or three-vessel disease. IPF was measured at admission by routine blood cells count (A Sysmex XE-2100). Results: We included in our study 2217 patients, of whom 544 had high levels of SUA, while 1673 had normal levels. Hyperuricemics were older, with higher percentage of renal failure, hypertension, dilated cardiomyopathy or valvular disease as indication to angiography, higher levels of creatinine and C-reactive protein (p < 0.001, respectively) when compared to normouricemics. Immature platelet fraction (IPF) was significant higher in hyperuricemic patients (3.96% vs 3.59%, p = 0.004). A progressive direct increase in the IPF values was observed in relation to SUA levels (r = 0.101, p < 0.001), although at multivariate analysis, hyperuricemia did not result as an independent predictor of IPC in 3rd tertile (adjusted OR [95%CI] = 1.21 [0.85–1.71] P = 0.288). When stratifying hyperuricemics and normouricemics according to IPF tertiles (<2.3%; 2.3–3.9%; ≥ 4%), reticulated platelets were not associated to the prevalence of CAD (SUA ≥6.5:80.9 vs 79.3% vs 78.6%, p = 0.60; SUA < 6.5: 79.3% vs 81.3% vs 78.9%, p = 0.878) or severe CAD (SUA ≥6.5: 34.9% vs 38.9% vs 35.2%, p = 0.99; SUA < 6.5: 30.4% vs 33.5% vs 34%, p = 0.192), and the results were confirmed at multivariate analysis for CAD (SUA ≥6.5: adjusted OR [95%CI] = 1.11 [0.81–1.51] P = 0.524, SUA < 6.5: adjusted OR [95%CI] = 0.89 [0.75–1.05] P = 0.170) or severe CAD (SUA ≥6.5: adjusted OR [95%CI] = 1.03 [0.81–1.31] P = 0.795; SUA < 6.5: adjusted OR [95%CI] = 1.10 [0.96–1.26] P = 0.192). Conclusions: In the present study we found a direct relationship between SUA levels and IPF values; however, hyperuricemia did not result as an independent predictor of higher IPF tertile values. Neither in hyperuricemics nor in normouricemics higher IPF were independently associated to the prevalence of CAD or severe CAD. Highlights: Immature platelet fraction (IPF) estimates the amount of circulating reticulated platelet. We aimed to investigate the impact of serum uric acid (SUA) on IPF in patients undergoing PCI. 2217 patients where included, 24.5% of whom displayed higher SUA levels. IPF values and SUA levels were found significantly directly related. Higher SUA did not predict higher IPF. In higher SUA patients IPF did not predict CAD prevalence and severity.